2007
DOI: 10.1007/s10339-007-0198-3
|View full text |Cite
|
Sign up to set email alerts
|

Emotional attention: effects of emotion and gaze direction on overt orienting of visual attention

Abstract: In the present study we considered the two factors that have been advocated for playing a role in emotional attention: perception of gaze direction and facial expression of emotions. Participants performed an oculomotor task in which they had to make a saccade towards one of the two lateral targets, depending on the colour of the fixation dot which appeared at the centre of the computer screen. At different time intervals (stimulus onset asynchronies, SOAs: 50,100,150 ms) following the onset of the dot, a pict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
31
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 37 publications
1
31
0
2
Order By: Relevance
“…Similarly, Bayliss et al (2007) demonstrated identical cueing effects for happy and disgusted faces. Bonifacci, Ricciardelli, Lugli, and Pellicano (2008) showed equivalent effects on overt orienting of gaze produced by angry and neutral faces (though the angry faces held attention, as described by Fox, Russo, & Dutton, 2002). That happy faces produce equivalent cueing effects as neutral faces is also supported by work by Holmes, Richards, and Green (2006) and Pecchinenda, Pes, Ferlazzo, and Zoccolotti (2008).…”
mentioning
confidence: 66%
“…Similarly, Bayliss et al (2007) demonstrated identical cueing effects for happy and disgusted faces. Bonifacci, Ricciardelli, Lugli, and Pellicano (2008) showed equivalent effects on overt orienting of gaze produced by angry and neutral faces (though the angry faces held attention, as described by Fox, Russo, & Dutton, 2002). That happy faces produce equivalent cueing effects as neutral faces is also supported by work by Holmes, Richards, and Green (2006) and Pecchinenda, Pes, Ferlazzo, and Zoccolotti (2008).…”
mentioning
confidence: 66%
“…In terms of stimulus-driven mechanisms, it has recently been shown that social attention is sensitive to facial cues other than gaze direction, such as facial physical self-similarity14, facial masculinity which provides cues of dominance1516, and emotional expressions1718. For example, Hungr and Hunt14 manipulated self-similarity by morphing the face of each participant with those of strangers and found a stronger gaze cueing effect when self-similar faces were created by morphing in equal proportion the participant's face with that of a stranger of the same gender (a manipulation that made explicit the recognition of the participants in the cueing face), suggesting that the perceived self-similarity of a distracting face influences the degree to which participants use gaze direction to orient their own attention14.…”
mentioning
confidence: 99%
“…Previous studies have used gaze cues embedded in a face stimulus to signal the location of an target [22,37]. The face is a complex stimulus.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, if the target appears in a different position from the cue, the attention must first be unlocked from the area indicated by the cue and then redirected to the new location. The high number of cognitive operations required to process an invalid target involves a great reaction time [21,22].…”
Section: Introductionmentioning
confidence: 99%